Sprint interval exercise elicits near maximal peak VO2 during repeated bouts with a rapid recovery within 2 minutes - Hazell, T. J.; Olver, T. D.; Macpherson, R. E.; Hamilton, C. D.; Lemon, P. W. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: We investigated the cardiorespiratory response during acute sprint interval exercise (SIE; 4 x 30 sec maximal efforts, each separated by 4 min recovery) vs. continuous endurance exercise (CEE; 30 min) at 70% VO2max.